Kontrastywna analiza formatu i tematyki wiadomości telewizyjnych w Polsce i Niemczech - Mac, Agnieszka (Stylistyka, 2021)
This paper aims to analyze TV news of selected public information magazine programs in Poland and Germany. The contrastive analysis encompasses TV news of the first German national channel ARD and the first Polish national channel TVP1. The focus of the analysis lies on the comparison of framed programs and information service topics broadcast in the two countries’ TV stations during the time when the main topie of all TV news both in Poland and Germany was the radical change in Egypt (selected information services in January and February in 2011). The following aspects have been thoroughly analyzed: service format, share of the hard news and the soft news as well as the national and intemational news of the information magazine during the given time as well as time dedicated to the main topie of the day.What can be inferred from the contrastive analysis of the information services of the national channels in Poland (TVP1) and Germany (ARD) is that the same information function performed within the same format may show many various differences. While the news on TVP1 seems to compete for larger audiences (i.e., greater share of the sensational news and soft news, the role of the anchor person), the ARD-news continues to prefer a certain sound tradition by offering a classical type of information service, stressing a serious national and intemational information. The decision to keep an unchanged TV news presentation guarantees the ARD-news a strong market share in the information sector among other public and commercial TV stations.